SOCIAL CONFLICT SETTLEMENT THROUGH REGULATION OF SURAT TUMBAGA HOLING IN BATAK ANGKOLA SOCIETY - Anwar Sadat Harahap; Ahmad Lahut Hasibuan (Faculty of Law, Universitas Jenderal Soedirman, 2016)
The main purpose of this research is to find the law setting model in preventing the social conflict through the regulation of Surat Tumbaga Holing in batak Angkola society. While the problem in this research is how the preventing model and settlement procedure of social conflict through regulation of Surat Tumbaha Holing. This research is using the empirical juridical research method. The reseach shows that the model of preventing social conflict based on regulation of Surat Tembaga Holing are settle by using: Sipaingot, Pastak-Pastak ni Paradaton, Uhum dohot Patik, Hapantunon, Tutur dohot Poda, Marga, Dalihan na Tolu, Martahi, Mangupa. This model used by batak society in order to solve the social conflict, so the potential of conflict that exist can be muted. Keywords: Prevention, Settlement, Social Conflict, Surat Tumbaga Holing, Batak Custom of Angkola